Digital photography for 3D imaging and animation - Ablan, Dan (Wiley Pub., 2007)
This practical and easy-to-follow book showa you how to transform your 3D projects with your own digital photographs and enhance your 3D animation by adding photographs that you’ve composed, lit, and shot. The featured tips and ideas will quickly have you creating quality photographs for use throughout the 3D workflow. From the mechanics of megapixels to the tricks of lighting to the art of finding the best images to shoot, you’ll learn valuable techniques that will transform your designs.